Public Administration and Sustainable Development in Nigeria - Okolie, Ugo Chuks; Ikenga, Francis A. (LPPM Universitas Malikussaleh, 2023)
This paper examined the predicaments facing Nigeria and how they have become more manifest in each attempt to attain democratic rule and economic reform. This approach provides an opportunity to observe how respect for human rights, democratization and broad-based sustainable development efforts have interacted with market-oriented economic policies in the past three decades in Nigeria. This paper adopted the analytical method and relies on secondary data and utilizes the content analysis for interpretation of data collected. The paper concludes that It is very critical for senior public administrators and political leaders to make the civil service employees to act ethically, not only in times of crisis or scandal, but on an everyday basis as well. It is also imperative for consideration to be given to ethics in hiring, performance evaluation, and promotion decisions, and that, if the civil service mission includes ethical behavior, then it should be evaluated along with other competencies.